Review of the Oriental genus Indocloeon Müller-Liebenau 1982 (Ephemeroptera: Baetidae) with descriptions of two new species - Kluge, Nikita J.; Suttinun, Chanaporn (Zootaxa, 2020)
The genus Indocloeon Müller-Liebenau 1982 (s. l.) is divided into two subgenera, the subgenus Indocloeon (s. str.) and the subgenus Hindocloeon subgen. n. which differ one from another by certain characters of larvae, winged stages and eggs. The subgenus Indocloeon is distributed in Sri Lanka only and includes two species, Indocloeon (Indocloeon) primum Müller-Liebenau 1982, and Indocloeon (Indocloeon) secundum sp. n., which are described here based on larvae, subimagines, imagines of both sexes and eggs associated by rearing. The subgenus Hindocloeon (type species Indocloeon indonesiae Kluge 2012) is widely distributed in the Oriental region. A new species Indocloeon (Hindocloeon) continentale sp. n. is described from Thailand based on larvae, subimagines, imagines of both sexes and eggs associated by rearing; subimagines presumably placed in this species, are reported from southern India. Some characters of Indocloeon (Hindocloeon) indonesiae Kluge 2012 are illustrated for the first time. The species originally described as Cloeon longistylus Demoulin 1969 is placed in Indocloeon as Indocloeon (Hindocloeon) longistylus comb. n. Subimagines of two unnamed species of Hindocloeon are reported from Vietnam and Java. Keys to known larvae and imagines are given.